Impact of customer participation in value co-creation on customer wellbeing: A moderating role of service climate - Yi, Xiaofang; Ul Haq, Junaid; Ahmed, Shehzad (Frontiers in Psychology, 2023)
The purpose of the study is to investigate consumer well-being because of consumer participation, value co-creation and customer resilience. This research identified the interaction effect of service climate in the presented context. The data was collected from 490 hotel customers. The structural equation modelling technique was used to observe the hypotheses testing. Participants of the study positively supported the impact of customer participation on customer well-being directly and indirectly. Moreover, results showed the partial mediation of customer resilience and value co-creation between customer participation and customer well-being. Service climates strengthen the relationship between customer participation and resilience and value co-creation. Theoretical and Practical implications have also been added.